2021
DOI: 10.1186/s12967-021-02838-x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status of Arab Gulf residents screened for SARS-CoV-2 and its association with COVID-19 infection: a multi-centre case–control study

Abstract: Objectives Vitamin D status in patients with COVID-19 is an on-going controversial issue. This study aims to determine differences in the serum 25(OH)D concentrations of Arab Gulf adult residents screened for SARS-CoV-2 and its association with risk of COVID-19 infection together with other comorbidities. Methods In this multi-center, case–control study, a total of 220 male and female adults presenting with none to mild symptoms were screened for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 47 publications
0
35
0
2
Order By: Relevance
“…To the best of our knowledge, the present study is the first clinical trial for vitamin D and COVID-19 conducted in the Middle East, a region with one of the highest prevalences of vitamin D deficiency in the world, especially in Saudi Arabia (SA) [ 13 , 16 , 20 ], which consequently, is one of the hardest hit by COVID-19 within the Gulf Cooperation Council (GCC) countries [ 1 ]. The goal of the present randomized clinical trial is primarily to determine whether a short-term 5000 IU vitamin D3 supplementation can reduce recovery times of COVID-19 symptoms among mostly in-patients with mild-moderate symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, the present study is the first clinical trial for vitamin D and COVID-19 conducted in the Middle East, a region with one of the highest prevalences of vitamin D deficiency in the world, especially in Saudi Arabia (SA) [ 13 , 16 , 20 ], which consequently, is one of the hardest hit by COVID-19 within the Gulf Cooperation Council (GCC) countries [ 1 ]. The goal of the present randomized clinical trial is primarily to determine whether a short-term 5000 IU vitamin D3 supplementation can reduce recovery times of COVID-19 symptoms among mostly in-patients with mild-moderate symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Among the well-established theories of this association is the biophysical and structural evidence that SARS-CoV-2’s point of cellular entry is the angiotensin converting enzyme 2 (ACE2) receptor protein, which is found in abundance on the surfaces of respiratory cells and is the same point of entry observed in SARS-CoV-1 [ 14 ]. Vitamin D heightens the expression of the ACE2 receptor protein, which balances the pathways that are known to be disrupted by coronaviruses, ACE/ACE2 and angiotensin II (ANG)/ANG 1-7 [ 15 , 16 ]. Another interesting theory is that vitamin D is a negative acute phase reactant in most acute and chronic inflammatory conditions [ 17 ], which also explains why vitamin D deficiency is common in states that harbor low-grade systemic inflammation such as diabetes, hypertension, heart disease, and aging [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a retrospective case–control study of 216 COVID-19 patients and 197 controls, Hernández et al did not find any relationship between serum 25(OH)D and the severity of the disease [ 40 ]. Additionally, the risk of Sars-CoV2 infection is not consistently related to the 25(OH)D serum concentration [ 41 ]. For example, Al-Daghri et al analyzed 138 patients with RT-PCR-confirmed Sars-CoV2 infection and 82 negative controls [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the risk of Sars-CoV2 infection is not consistently related to the 25(OH)D serum concentration [ 41 ]. For example, Al-Daghri et al analyzed 138 patients with RT-PCR-confirmed Sars-CoV2 infection and 82 negative controls [ 41 ]. Although Sars-CoV2 patients had lower 25(OH)D concentrations than non-infected controls, Al-Daghri et al could not show a higher risk of Sars-CoV2 infection in individuals with low 25(OH)D concentrations [ 41 ].…”
Section: Discussionmentioning
confidence: 99%